A Cognitive Linguistic Study of Verb-copying Sentences in Mandarin Chinese - Xu, Yuting (Advances in Social Sciences Research Journal, 2020)
This study concerns the verb-copying structure “S+V+Object+V+Resultative” in Chinese from the perspective of cognitive grammar. It views the construction as composited from component structure “S+V+Object” and “V+Resultative” and reveals the compositional path and mental representation of this construction. The results indicate that component SVO elaborates the schematic trajector of V in Component VR. This conceptual correspondence lays the foundation for the integration of component SVO and VR, which constitutes the internal motivation of SVOVR construction. Component SVO serves as the cognitive reference point for the conceptualization. The elements in the dominion of action that SVO designates are extracted as conceptualization target. SVOVR construction is organized in the pattern of Baseline and Elaboration. In local terms, each stratum provides the potential for the next and the conceptualization result - the linear structure - is completed in a cumulative fashion. In global terms, component SVO and VR serve as dual baseline whose mutual elaboration yields a composite structure of greater complexity. SVOVR construction imposes some restrictions on the repeated verb. The verb needs to designate the actions that can be repeated and continued. Structure One cannot have any tense or the aspect markers. SVOVR construction does not stand in isolation from other units in linguistic system; it is categorized by the conventionalized SVO structure and predicate-complement VR structure in Chinese language system, which is the external motivation for this construction.